Influência da poluição atmosférica por SO2, MP10, MP2,5 e sua composição elementar na incidência de doença respiratória aguda em crianças - Nascimento, Antônio Paula (2015)
The aim of this study is to investigate the influence of atmospheric pollutants such as SO2, MP10 and MP2,5 in acute outcome of respiratory diseases in 12-year old children living in urban and industrial areas and to ascertain the influence of inorganic elements, as well as elemental carbon present in fine particulate (MP2,5) in those outcome within short periods, during Winter and Summer times in the South hemisphere. Data on SO2 e MP10 concentrations were obtained through measurements made in six stations of the air quality automatic monitoring net placed in the Great Vitoria Metropolitan Region (RMGV). Samples of MP2,5 were collected in the same region using the MiniVol sampler during a 24-hour period in alternate days. They were weighted in a scale with 1 μm sensitivity and the analysis of its components was carried out using the energy dispersion X-Ray fluorescence technique and by the reflectance technique. Cases of common health care as well as hospital patient admissions due to acute respiratory diseases in CID-10 JJ00 - JJ99 groups were obtained in three hospitals (one public and two private). All data were obtained during the Winter (from 21/06/2013 to 21/09/2013) and the Summer (from 21/12/2013 to 19/03/2014). To quantify the correlation between acute respiratory diseases to the pollutant concentrations the Generalized Additive Model (GAM) with Poisson distribution was applied. Results have pointed out greater relative risk (RR) of acute respiratory events due to the presence of SO2, a 1,28 RR (IC 95%: 1,22 – 1,34) and MP10, a 1,14 RR (IC 95%: 1,09 – 1,20), within the day of exposure (lag 0). With respect to fine particulate, exposure effects have shown more evident effects after a six-day period from the exposure, with a 1,05 RR (I.C. 95%: 1,01 – 1,10). Chemical components present in fine particulate showing a larger RR of causing acute respiratory diseases were: Si – 1, 22 RR (IC 95%: 1,15 – 1,29), S – 1,09 RR (IC 95%: 1,06 – 1,12), Ti – 1,09 RR (IC 95%: 1,01 – 1,17), the black carbon (BC) – 1,07 RR (IC 95%: 1,03 – 1,11) for a same day occurrence of exposure and outcome. For outcomes due to a two-day period after exposure, the greatest RR of respiratory diseases in the short term is associated with the presence of Se –1,14 RR (IC 95%: 1,06 – 1,23) and Ni – 1,10 RR (IC 95%: 1,02 – 1,19).